Lived Experiences of Filipino Student-Mothers in Night Shift Undergraduate Classes - Gonzales, Jomar R; Paglingayen, Mae Anne C (ASEAN Multidisciplinary Research Journal, 2022)
It is a daunting task to balance the life of motherhood and student hood. In addition to the responsibilities of being a mother and a student are the requirements of academic and personal life; especially, during the time of COVID-19 pandemic. According to studies, for generations, student-mothers in the Philippines, who decided to continue their academic endeavor despite their struggles in academic and parenthood duties. In this phenomenological study, the lived experiences of five (5) night class student-mothers to young children during the pandemic had undergone one-on-one and panel group online interviews. The respondents were chosen via purposive sampling. The student-mothers were from Pangasinan State University-Bayambang Campus. The instrument used was researchers-made semi-structured interview guide questionnaire and was validated by experts in the field of psychology and education. Results revealed that most of the participants encountered difficulties regarding their personal and academic lives like work and financial issues, attending online classes, distractions and concentrations during online classes, limited availability of digital resources, and proper time management. To cope with these challenges, the participants relied on the support provided by their classmates, friends, families, and religious beliefs. Also, the results imply that academic institutions may consider intervention programs for night class student-mothers who are attending online classes during this time of COVID-19 pandemic, and create webinar workshops that may empower them to better manage their dual roles of being a mother and a student.